The U.S. Low-Wage Structure: A McWage Comparison - Orley Ashenfelter; Štepán Jurajda (Institute of Labor Economics (IZA), 2024)
Thanks to standardized work protocol and technology of McDonald's restaurants, the hourly wage of McDonald's Basic Crew enables wage comparisons under near-identical skill inputs and hedonic job conditions. McWages capture labor costs in entry-level jobs, while the Big Macs (earned) Per Hour (BMPH) index measures corresponding purchasing power of wages. We document large and growing geographical wage differences in standardized jobs using data covering most U.S. counties during 2016-2023. Before the Covid-19 pandemic, there was no BMPH growth where minimum wages stayed constant, but the pandemic wage increase, which diminished the importance of minimum wages, was stronger in these areas.
Keywords: J31; 330; McWages